2023
DOI: 10.1038/s41591-023-02427-z
|View full text |Cite|
|
Sign up to set email alerts
|

The FGF21 analog pegozafermin in severe hypertriglyceridemia: a randomized phase 2 trial

Abstract: Pegozafermin, a long-acting glycopegylated analog of human fibroblast growth factor 21, is in development for the treatment of severe hypertriglyceridemia (SHTG) and nonalcoholic steatohepatitis. Here we report the results of a phase 2, double-blind, randomized, five-arm trial testing pegozafermin at four different doses (n = 67; 52 male) versus placebo (n = 18; 12 male) for 8 weeks in patients with SHTG (triglycerides (TGs), ≥500 mg dl−1 and ≤2,000 mg dl−1). Treated patients showed a significant reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…FGF21 has been hypothesised to be high in vegans as a downstream effect of low intake of methionine [15], an essential amino acid that is known to be limiting in vegan diets [3]. Studies of FGF21 administration in rodents have found favourable effects on adiposity, lipid profiles, and non-alcohol fatty liver disease, but possible adverse effects on bone homeostasis [22]; randomised trials of FGF21 analogues also support the reduction in triglycerides [23] and improvement of fibrosis in patients with non-alcoholic steatohepatitis [24]. Consistent with these observations, we have previously reported lower BMI and body fat [25], more favourable lipid profiles [26] and lower heart disease risk [27], but also lower bone mineral density [25] and higher fracture risk [28] in vegetarians and vegans when compared with meat eaters; another study has reported lower odds of non-alcohol fatty liver disease in vegetarians than non-vegetarians [29].…”
Section: Discussionmentioning
confidence: 99%
“…FGF21 has been hypothesised to be high in vegans as a downstream effect of low intake of methionine [15], an essential amino acid that is known to be limiting in vegan diets [3]. Studies of FGF21 administration in rodents have found favourable effects on adiposity, lipid profiles, and non-alcohol fatty liver disease, but possible adverse effects on bone homeostasis [22]; randomised trials of FGF21 analogues also support the reduction in triglycerides [23] and improvement of fibrosis in patients with non-alcoholic steatohepatitis [24]. Consistent with these observations, we have previously reported lower BMI and body fat [25], more favourable lipid profiles [26] and lower heart disease risk [27], but also lower bone mineral density [25] and higher fracture risk [28] in vegetarians and vegans when compared with meat eaters; another study has reported lower odds of non-alcohol fatty liver disease in vegetarians than non-vegetarians [29].…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies vary according to drug, dose and duration of treatment. However, generally, reductions of up to 69% in TG, 30% in LDL-C, 34% in non-HDL-C and 25% in apoB and an increase of up to 61% in HDL-C are observed [ 60 , 61 ]. In the study of non-alcohol-related steatohepatitis (NASH) [ 60 ], the liver fat fraction was reduced after treatment with the FGF21 analogue.…”
Section: Therapies Mainly Targeting Triglycerides/hdl-cholesterolmentioning
confidence: 99%
“…In patients with severe HTG (i.e. ∼500–1000 mg/dl) at increased risk of nonalcoholic fatty liver disease (NAFLD) may also benefit from treatment with the fibroblast growth factor 21 (FGF21) analog, pegozafermin, based upon the appreciable reduction in liver fat observed over a 2-month interval [ 45 ▪▪ ]. Pemafibrate may also be a consideration in view of the 22% reduction in Investigator-reported NAFLD in PROMINENT [ 7 ] and improved biomarkers of liver fibrosis in patients with NAFLD and less severe HTG [ 46 ▪▪ ].…”
Section: Triglyceride-lowering Therapies To Reduce Cardiovascular Dis...mentioning
confidence: 99%